2007
DOI: 10.1242/jcs.003954
|View full text |Cite
|
Sign up to set email alerts
|

Cell adhesion to fibrillin-1: identification of an Arg-Gly-Asp-dependent synergy region and a heparin-binding site that regulates focal adhesion formation

Abstract: We have defined the molecular basis of cell adhesion to fibrillin-1, the major structural component of extracellular microfibrils that are associated with elastic fibres. Using human dermal fibroblasts, and recombinant domain swap fragments containing the Arg-Gly-Asp motif, we have demonstrated a requirement for upstream domains for integrin-α5β1-mediated cell adhesion and migration. An adjacent heparin-binding site, which supports focal adhesion formation, was mapped to the fibrillin-1 TB5 motif. Site-directe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(105 citation statements)
references
References 29 publications
4
100
1
Order By: Relevance
“…These assemblies were reminiscent of cell-surface LTBP-1 in an earlier scanning-EM study (Taipale et al, 1996). Although both fibrillin-1 and LTBP-1 partially colocalized with fibronectin, exogenous heparin blocked deposition of both LTBP-1 and microfibrils, but not fibronectin; this deposition was most probably blocked by heparin directly competing with heparan-sulfate-dependent fibrillin-1 terminal assembly interactions (Cain et al, 2008) and interactions with syndecans (Bax et al, 2007). Exogenous heparin might also compete with other matrix interactions that depend on cell-surface heparan sulphate.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…These assemblies were reminiscent of cell-surface LTBP-1 in an earlier scanning-EM study (Taipale et al, 1996). Although both fibrillin-1 and LTBP-1 partially colocalized with fibronectin, exogenous heparin blocked deposition of both LTBP-1 and microfibrils, but not fibronectin; this deposition was most probably blocked by heparin directly competing with heparan-sulfate-dependent fibrillin-1 terminal assembly interactions (Cain et al, 2008) and interactions with syndecans (Bax et al, 2007). Exogenous heparin might also compete with other matrix interactions that depend on cell-surface heparan sulphate.…”
Section: Discussionmentioning
confidence: 74%
“…We have shown that unprocessed N-terminal fibrillin-1 fragment PF1 interacts with cells in a heparan-sulfate-dependent manner (Bax et al, 2007), whereas heparin induces a very high heparin- Ex1-11 and PF1 showed only weak binding to full-length LTBP-1 (not shown). (B)BIAcore analysis of the binding of C-terminal LTBP-1 (C-LTBP-1), immobilized on a CM5 chip, to PF1 (i), PF1 (ii) or PF1 Ex6+7 (iii).…”
Section: Binding Of Full-length Ltbp-1 To Pro-fibrillin-1 Is Facilitamentioning
confidence: 89%
“…To evaluate how adhesion to ECM regulates PDGFR activation in MSCs, tyrosine phosphorylation of PDGFR-a and PDGFR-b was examined in serum-free conditions, after plating onto fibronectin, laminin, fibrillin-1 PF8 [an Arg-Gly-Asp (RGD)-containing fragment that engages the a5b1-integrin] (Bax et al, 2007;Cain et al, 2005), collagen type I or collagen type IV (all at 10 g/ml) for 90 minutes. A human array for phosphorylated RTKs (Fig.…”
Section: Adhesion To Ecm Induces Pdgfr Tyrosine Phosphorylationmentioning
confidence: 99%
“…Fibrillin can often be found by itself, in which it may independently function as a mechanical, load-bearing but highly extensible scaffold [40]. Numerous domains in fibrillin exist for binding integrins, heparan sulafate proteoglycans, and growth factors, which point to substantial roles for alone fibrillin and mature elastic fibers in mediating cell signaling and adhesion [41].…”
Section: Elastic Fibers Comprise a Significant Portion Of The Ventricmentioning
confidence: 99%